Lateralisation of visual function in yellow-eyed mullet (Aldrichetta forsteri) and its role in schooling behaviour. Issue 1 (2nd January 2018) - Middlemiss, Karen L.; Cook, Denham G.; Jaksons, Peter; Jerrett, Alistair R.; Davison, William
Abstract: Lateralisation of cognitive function is a common phenomenon found throughout the animal kingdom. In fish, lateralisation is involved in visually mediated behaviours such as schooling, predator avoidance and foraging. This study sought to quantify visual laterality in yellow-eyed mullet ( Aldrichetta forsteri ), to determine visual asymmetries and the significance of lateralisation, and the factors which influence functional behaviours in schooling fish. Tank-based experiments investigated individual and population level lateralisation, schooling behaviour, and optic lobe asymmetry. Variation in direction and strength of lateralisation in individuals was found in juveniles, but at a population level significant bias was found in adults. Right eye biased fish had a larger right optic lobe than control fish. Strongly lateralised fish showed a tendency to occupy positions of safety within the school more frequently than control fish. In combination with observed differences in schooling behaviour, the possibility of ontogenetic plasticity in behavioural lateralisation and optic lobe morphology is suggested.